W poszukiwaniu romanizacji...; rec. książki: Colonisation and Romanization in Moesia Inferior. Premises of a contrastive approach, red. Lucretiu Mihailescu-Birliba - Mrozewicz, Leszek (Studia Europaea Gnesnensia, 2016)
.